Job satisfaction of female employees in microfinance institutions of Bangladesh - Uddin, Md Nazim; Hamdan, Hamdino; Che Embi, Nor Azizan; Kassim, Salina; Md Saad, Norma (Insight Publisher, 2020)
The purpose of this study is to examine the level of female employee satisfaction regarding their job of microfinance institutions in Bangladesh. Furthermore, it concentrates on the different elements that impact female employee job satisfaction of Microfinance Institutions (MFIs). The research used quantitative analysis methods and used Herzberg’s motivation-hygiene theory (1959). A total of 24 structured questionnaires with five proportions have been provided to 100-woman participants of chosen MFIs in Bangladesh. The findings reveal that some variables (performance-based salary increase, obtainable possibilities for promotion, satisfaction on job environment, co-workers help during large workload, chance to interact with other workers on a formal level, usage of skill, knowledge & qualification, acknowledgement for exceptional function, and learning opportunity) have significant effect on female employee satisfaction in MFIs. The limitation of the researched investment fund can be that it invests in growing and mature MFIs. Therefore, the outcomes of this analysis can only become generalised to growing and mature MFIs. This research goals at contributing to better female workers job satisfaction of the MFIs if it has considerable implications on economic benefit, job environment, job security, decision making training and resources of the MFIs.